PENDEKATAN RESTORATIF DALAM PENJATUHAN SANKSI TINDAKAN BAGI ANAK YANG BERKONFLIK DENGAN HUKUM - citra (FAKULTAS HUKUM UM PAREPARE, 2019)
Children are the next generation of the nation, the existence of children is very important because the child is a potential fate of the nation as well as a mirror attitude of life of the nation in the future. A child who is a superior seed and has the widest hope to prepare for his future as a milestone of success of a nation in the future should not fall in the world of evil. It is unfortunate that children at an early age have been involved in criminal offenses and past their youth behind bars, increasingly contaminated with other inmates. This research was empirical legal research, that is the research on the provisions of the legislation in the national law concerning restorative approach in the imposition of action sanctions against children in conflict with law in order to keep children away from imprisonment and negative stigma in society . Addressing the issue of a child in conflict with the law should be done in a familial approach and avoiding children from prison as much as possible. The sanction of action for the child contained in Article 82 of Law Number 11 of 2012 on Criminal Justice System for Children expected to prevent the child from the negative stigma in society and keep the children from bad effects of prison. Thus the current restorative model of punishment is more applicable in handling child offenders. It is expected that law enforcement officers to pay attention to the provisions of the rules that apply to children in conflict with the law in terms of imposition of more sanctions toward education and character development of children so that the threat of imprisonment becomes the last alternative in imposing sanctions for children